Analisis Hukum terhadap Janji Asuransi yang Tidak Realistis: Perlindungan Hukum Bagi Nasabah - Herbin Saragi; Rangga Aufar; Dina Napitupulu (Syntax Corporation Indonesia, 2025)
Insurance companies often use attractive promises of benefits as a marketing strategy to attract potential customers. However, in some cases, these promises are unrealistic and cannot be fulfilled, which ultimately harms the client. This study aims to analyze the legal aspects that regulate unrealistic insurance promises and their impact on legal protection for customers in Indonesia. This study uses normative juridical methods, this study examines applicable laws and regulations, such as Law Number 8 of 1999 concerning Consumer Protection and Law Number 40 of 2014 concerning Insurance, as well as cases that occur in Indonesia related to unreasonable insurance promises. The results of the study show that despite regulations that protect consumers, the practice of selling insurance that is not transparent still often occurs. The study recommends that insurance companies increase transparency and the government tighten supervision to ensure that customer rights are well protected.